THE INITIATION, RESPONSE, AND FEEDBACK (IRF) IN ENGLISH LANGUAGE TEACHING: A LITERATURE REVIEW - Dalia, Arisa Cahyalaili; Putra, Fahry Rizaldy (LPPM STBA Pontianak, 2024)
Initiation between teachers and students is the foundation for classroom discourse. Multiple models for classroom discourse could improve the initiation between the teacher and students in the classroom. It is presumptively true that classroom discourse